Development of High School Biology Students Worksheets Based on Critical Thinking Skills on the Concept of the Digestive System - Rindi Antika; Muhammad Zaini; Muhammad Arsyad (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2020)
One of the problems of life that are happening right now is the problem in education. Three skills need to be improved including 1) the field of cognitive skills, 2) interpersonal skills, and 3) intrapersonal skills. The purpose of this study is to improve the Student Worksheet (LKPD) so that it has effective criteria. The use of LKPD in the learning process is expected to improve students' critical thinking skills. The research method used is the Tessmer design using a small group test. Critical thinking skills refer to Facione 1990 while the structure of LKPD development refers to Daryanto & Dwicahyono. The small group test subjects were six high school class XI students. This research is development research using Tessmer design. The study was conducted for one semester, namely in the 2019-2020 school year. The results showed that the effectiveness of LKPD based on the assessment of students' critical thinking skills in working on LKPD had a category of at least good, interpersonal skills had a very good category, and intrapersonal skills had a very good category.AbstrakSalah satu permasalahan kehidupan yang terjadi saat ini ialah permasalahan pada pendidikan. Terdapat 3 keterampilan yang perlu ditingkatkan diantaranya 1) bidang keterampilan kognitif, 2) keterampilan interpersonal, dan 3) keterampilan intrapersonal. Tujuanudariupenelitian ini ialah memperbaiki Lembar Kerja Peserta Didik (LKPD) sehingga memiliki kriteria efektif. Penggunaan LKPD dalam proses pembelajaran diharapkan dapat meningkatkan keterampilan berpikir kritis peserta didik. Metode penelitian yang digunakan yaitu desain Tessmer menggunakan uji kelompok kecil. Keterampilan berpikir kritis mengacu pada Facione 1990 sedangkan struktur pengembangan LKPD mengacu pada Daryanto & Dwicahyono. Subjek uji kelompok kecil adalah 6 orang peserta didik kelas XI jenjang SMA. Penelitian ini adalah penelitian pengembangan menggunakan desain Tessmer. Penelitian dilakukan selama satu semester yaitu pada tahun ajaran 2019-2020. Hasil penelitian menunjukkan bahwa keefektifan LKPD berdasarkan penilaian keterampilan berpikir kritis peserta didik dalam mengerjakan LKPD memiliki kategori sekurang-kurangnya baik, keterampilan interpersonal memiliki kategori sangat baik, dan keterampilan intrapersonal memiliki kategori sangat baik.